2014
DOI: 10.14257/ijsh.2014.8.2.08
|View full text |Cite
|
Sign up to set email alerts
|

An Improved MAC Protocol for WBAN Through Modified Frame Structure

Abstract: In WBAN environment, it is important to achieve energy efficiency of nodes implanting into human body. At the same time, a master also plays an important role in collecting data from nodes and controlling the nodes. By maintaining a master properly, any kinds of situation can be handled. Therefore, low power MAC protocol between a master and a node is highly required appropriately. A MAC protocol proposed in this paper aims to satisfy with these requirements and improve energy consumption rate that tends to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The Superframe structure of MAC [45] comprises of Exclusive Access Periods (EAP-I/ II), and Random Access Periods (RAP-I/II) using Traffic types Type-I and Type-II. The EAP-I and EAP-II are used to transmit emergency data with the support of TYPE-I.…”
Section: Predefined and Prediction Based Slot Allocationmentioning
confidence: 99%
“…The Superframe structure of MAC [45] comprises of Exclusive Access Periods (EAP-I/ II), and Random Access Periods (RAP-I/II) using Traffic types Type-I and Type-II. The EAP-I and EAP-II are used to transmit emergency data with the support of TYPE-I.…”
Section: Predefined and Prediction Based Slot Allocationmentioning
confidence: 99%
“…However, the proposal has been long circulating (79 circulations as of now) with mixed approval rates [31]. Additionally, as indicated in several studies [32] [33], the technology has a limited support of medical systems, such as patient monitoring systems that require reliable throughput assurance for monitoring patient life functions. Timmons et al [34] also demonstrated undesirably high power consumption of IEEE 802.15.6 (25.6% -33.2% higher than their baseline framework).…”
Section: Related Workmentioning
confidence: 99%
“…WBAN supports a wide range of medical and Consumer Electronics (CE) applications [1]. A wireless body sensor network (WBSN) environment is an applied network that was advanced from a WBAN environment [2], that allows communication within a body based on wireless sensor networks (WSNs) [3]. It is an environment where the condition of a patient is monitored in real time by collecting various data from the tools or node transplanted inside or outside the body.…”
Section: Introductionmentioning
confidence: 99%